Evaluation of tourism ecological security and its obstacles in semi-arid river valley urban: a case study of Lanzhou, China - Kejun Wu; Mengtao Wu; Zhihai An; Hui Jiao (Scientific Reports)
Abstract Assessing tourism ecological security is essential for balancing development with environmental sustainability, thereby guiding effective resource management and policy formulation within the tourism industry. This study evaluates the ecological security of Lanzhou’s tourism sector, a city rich in historical and natural resources yet facing unique ecological challenges. Our objectives were to assess the current status of tourism ecological security in Lanzhou and provide actionable policy recommendations. We employed a comprehensive evaluation framework that integrates both qualitative and quantitative methods, including the DPSIR model, mean square deviation, and entropy methods for weight calculation, as well as TOPSIS for overall assessment and coupled coordination degree and obstacle degree models for subsystem analysis. The results indicate an upward trend in Lanzhou’s tourism ecological security from 2009 to 2021, peaking in 2019 before experiencing a pandemic-induced decline in 2020–2021. While subsystem coupling coordination generally improved, the pressure and state subsystems exhibited instability. These findings offer valuable insights for similar regions and underscore the necessity for holistic management strategies. We recommend enhancing ecological monitoring, promoting sustainable tourism practices, and enhancing local community involvement in tourism management. These measures are crucial to improving Lanzhou’s tourism ecological security and could serve as a model for other cities with similar development trajectories. Future research should focus on refining ecological security evaluation models and exploring the broader socio-economic impacts of ecological sustainability in tourism.